1992
DOI: 10.1111/j.1439-037x.1992.tb01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Forage Potentials of Pearl Millet in a Semi‐arid Tropical Environment

Abstract: The pastures and rangelands of the semi‐arid region of Nigeria wherein is the bulk of the livestock in the country, provide sufficient nutrients for livestock for no more than three to five months of the year. There is therefore need to have high yielding and good quality forages to ensure adequate all‐year‐round forage supply for the livestock. The objective of this study was to evaluate the forage potentials of pearl millet (Pennistetum americanum [L.] K. Schum.) which is well adapted to the region. Twenty c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
2
4
0
1
Order By: Relevance
“…A dry matter yield of 8.57 tons/ha obtained by the Malgorou variety at the dough stage was higher than recorded yields of rain fed forage millet with multiple cuttings (Craufurd and Bidinger 1989) and similar to forage yields obtained under high fertilization regimes (Reddy et al, 2003). It is comparable to dry matter yield from four cuttings in a higher rainfall area in north Nigeria (Makeri and Ugherughe (1992). Analysis of variance showed that planting densities had significantly affected dry matter yield (P<0.05).…”
Section: Dry Matter Productionsupporting
confidence: 52%
See 1 more Smart Citation
“…A dry matter yield of 8.57 tons/ha obtained by the Malgorou variety at the dough stage was higher than recorded yields of rain fed forage millet with multiple cuttings (Craufurd and Bidinger 1989) and similar to forage yields obtained under high fertilization regimes (Reddy et al, 2003). It is comparable to dry matter yield from four cuttings in a higher rainfall area in north Nigeria (Makeri and Ugherughe (1992). Analysis of variance showed that planting densities had significantly affected dry matter yield (P<0.05).…”
Section: Dry Matter Productionsupporting
confidence: 52%
“…For this reason very little research has been conducted on millet forage production in the Sudano Sahel under rainfed conditions. Makeri and Ugherughe (1992) is an exemption. These workers compared the productivity and some quality parameters of 20 pearl millet varieties in northern Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…) and Ca (1.230 to 2.180 g kg -1 ) contents in the present study were much higher than the dietary Mg and Ca requirements of beef and dairy cattle which are between 0.4 and 1.8 g kg -1 (Makeri and Ugherughe, 1992). Also, the variability among inbred lines and their hybrids followed similar trends as P and Ca, with CV value of 8.07%.…”
Section: Resultssupporting
confidence: 50%
“…Comportamento inverso foi obtido na PMSC, que foi de 242 kg ha -1 no primeiro corte, e 922 kg ha -1 , no quarto corte. Makeri & Ugherughe (1992) atribuíram o decréscimo gradual na produção de folhas em cultivares de milheto ao avanço na maturidade das plantas.…”
Section: Resultsunclassified